2013
DOI: 10.1007/s00011-013-0681-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-arthritic effects of 3-hydroxy, 2-methoxy sodium butanoate from the leaves of Clerodendrum phlomidis L.f.

Abstract: The 3-hydroxy,2-methoxy sodium butanoate isolated from plant leaves displays considerable potency in anti-inflammatory action and has a prominent anti-arthritic effect. This is the first report of this natural compound with bioactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…A direct engagement of lysosomal enzymes with connective tissue degrades its components such as collagen, protein‐bound carbohydrates, glycosaminoglycans and elastin and thus plays a prime role in alleviating the arthritic condition. Moreover, lysosomal glycohydrolases open up the collagen fibres for the direct action of collagenolytic enzymes which reflects the cartilage destruction with elevated levels of urinary hydroxyproline . Results obtained through our study are at par with the above findings.…”
Section: Discussionsupporting
confidence: 83%
“…A direct engagement of lysosomal enzymes with connective tissue degrades its components such as collagen, protein‐bound carbohydrates, glycosaminoglycans and elastin and thus plays a prime role in alleviating the arthritic condition. Moreover, lysosomal glycohydrolases open up the collagen fibres for the direct action of collagenolytic enzymes which reflects the cartilage destruction with elevated levels of urinary hydroxyproline . Results obtained through our study are at par with the above findings.…”
Section: Discussionsupporting
confidence: 83%
“…This plant is also used as a traditional medicine in India, Bangladesh, Pakistan and surrounding areas, especially for joint pain medication. One study found that C. phlomidis leaf extract had anti-inflammatory and anti-arthritic activity using carrageenan-induced paw edema and arthritis induced with FCA (Freund complete adjuvant) in trial rats (Prakash et al 2014). Other studies also reported the same founding in the root extract of C. phlomidis using granuloma cotton pellet method (Parekar et al 2012).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, HMSB could significantly down-regulate pro-inflammatory cytokines TNF, IL-1 and IL-6 protein levels and mRNA expression in the joints with a dose-dependent manner. 90 These results indicated that the HMSB possess considerable potency in anti-inflammatory action and has a prominent anti-arthritic effect. Panthong et al evaluated the anti-inflammatory and antipyretic activities of the methanol extract (at doses of 1.0, 2.0, 4.0 mg/ear, i.g.)…”
Section: Pharmacological Propertiesmentioning
confidence: 91%
“… Anti-inflammatory and anti-nociceptive activity 3-Hydroxy, 2-methoxy-sodium butanoate In vivo Carrageenan-induced inflammation and freund complete adjuvant (FCA)-induced arthritic rat models 25, 50, 100 mg/kg, i.g. Reduced the paw edema response, decrease lysosomal enzymes, protein-bound carbohydrates, and acute phase protein levels 90 Methanol extract from C. petasites In vivo Ethyl phenylpropiolate-induced ear edema and carrageenan-induced paw edema in rats 1, 2, 4 mg/ear, i.g. Inhibited prostaglandin synthesis 91 Ethanol extract from C. laevifolium in vitro lipoxygenase 10–1000 μg/ml Displayed the greatest inhibition capacity with the IC 50 value of 14.12 μg/ml 92 Methanolic extract from C. inerme In vivo Formalin induced hind paw edema animals 50, 100, 200 mg/kg, i.g.…”
Section: Pharmacological Propertiesmentioning
confidence: 98%